Direct Result for a Summation-Integral Type Modification of Szász-Mirakjan Operators (Analysis in Theory and Applications, 2020)
In this paper, study of direct result for a summation-integral type modification of Szász-Mirakjan operators is carried out. Calculation of moments, density result and a Voronovskaja-type result are also obtained.
Keywords: Szász-Mirakjan operators; K-functional; modulus of smoothness; Voronovskaja-type result.